Comparative genomic analysis of the IId subtype family of Cryptosporidium parvum. Issue 5 (April 2017) - Feng, Yaoyu; Li, Na; Roellig, Dawn M.; Kelley, Alyssa; Liu, Guangyuan; Amer, Said; Tang, Kevin; Zhang, Longxian; Xiao, Lihua
Graphical abstract: Highlights: Genomes of three Cryptosporidium parvum isolates were sequenced. Sequence data were obtained for >99.3% of the expected genome. Host-adapted IIa and IId subtype families have different numbers of subtelomeric genes for three secretory protein families. Highly polymorphic genes between IIa and IId encode mostly invasion-associated secretory mucin proteins. These genomics features could be involved in phenotypic differences among C. parvum isolates. Abstract: Host adaptation is known to occur in Cryptosporidium parvum, with IIa and IId subtype families preferentially infecting calves and lambs, respectively. To improve our understanding of the genetic basis of host adaptation in Cryptosporidium parvum, we sequenced the genomes of two IId specimens and one IIa specimen from China and Egypt using the Illumina technique and compared them with the published IIa IOWA genome. Sequence data were obtained for >99.3% of the expected genome. Comparative genomic analysis identified differences in numbers of three subtelomeric gene families between sequenced genomes and the reference genome, including those encoding SKSR secretory proteins, the MEDLE family of secretory proteins, and insulinase-like proteases. These gene gains and losses compared with the reference genome were confirmed by PCR analysis. Altogether, 5, 191–5, 766 single nucleotide variants were seen between genomes sequenced in this study and the reference genome, with most SNVs occurring in subtelomeric regions of chromosomes 1, 4, and 6. The most highly polymorphic genes between IIa and IId encode mainly invasion-associated and immunodominant mucin proteins, and other families of secretory proteins. Further studies are needed to verify the biological significance of these genomic differences.